Aquaman. Vol. 1, The dark tide - Adams, Jeremy (Screenwriter) (DC Comics, 2025)
The king is back, baby! Aquaman stars in his first solo series in years as a major part of DC's bestselling, new-reader-friendly All In initiative! In the wake of the blockbuster DC event Absolute Power, Arthur Curry's powers have evolved to powerful new heights, and this is one king ready to use them to kick some serious butt. Mammoth water-construct Kaijus have emerged from each of the seven seas, and only Aquaman's water-warping abilities can stop them--but not if they kill the good king in the process! Enter Dagon, Arthur's guide on the quest to unlock the secrets of the "blue." But what deadly secret awaits Arthur on his journey? An all-new era of Aquaman begins, courtesy of the splashy creative team of writer Jeremy Adams (the architect of fan-favorite runs on The Flash and Green Lantern) and artist John Timms (known for his amazing visuals on Harley Quinn and Action Comics)! This high-energy new take on Earth's uncanny undersea hero will leave you cheering!